Supply Chain 4.0: Impact on Operational Performance, Mediated by Enterprise Resource Planning - Julian, Antonio Asa; Purba, Heddry; Rinendy, Jhon (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Digitalization has driven companies to invest in enhancing their Supply Chain towards Supply Chain 4.0, where digital system integration becomes a key factor in improving operational performance. In this context, Enterprise Resource Planning (ERP) plays a crucial role in optimizing supply chain processes through more structured digitalization. This study employs a quantitative method using purposive sampling, involving 100 respondents. Data was collected through a questionnaire measured using a Likert scale. The data analysis technique utilized is Structural Equation Modelling Partial Least Square (SEM-PLS). The findings reveal that the implementation of digital supply chain has a significant positive impact on operational performance. Although DSC has a direct influence on operational performance, its impact is not as substantial as when mediated through ERP. This confirms the mediation analysis, indicating that ERP implementation plays a vital role in strengthening the influence of digital supply chain transformation on operational performance.